FIXED DRUG ERUPTION DUE TO HEPARIN INJECTION - Shaheen, Shagufta; Akhtar, Shahnaz (Journal of Postgraduate Medical Institute, 2011)
This case report describes a young female with fixed drug eruption due to heparin injection and treatment by surgical debridement.